Proposed Negative Statutory Instruments under the European Union (Withdrawal) Act 2018 : Energy Efficiency (Private Rented Property) (England and Wales) (Amendment) Regulations 2018 / Includes a Recommendation on the following : Merchant Shipping (Marine Protection) (Amendment etc.) (EU Exit) Regulations 2018 ; Energy Efficiency (Private Rented Property) (England and Wales) (Amendment) Regulations 2018 ; Correspondence : Building (Amendment) Regulations 2018 : 10th Report of Session 2017-19 /: Includes a Recommendation on the following : Merchant Shipping (Marine Protection) (Amendment etc.) (EU Exit) Regulations 2018 ; Energy Efficiency (Private Rented Property) (England and Wales) (Amendment) Regulations 2018 ; Correspondence : Building (Amendment) Regulations 2018 : 10th Report of Session 2017-19. ([2018-12-19]) - Unknown
No abstract available